Penggunaan Aplikasi Mobile Untuk Pengelolaan Zakat - Kamizi, Fajar; Pramudita, Adinda (J-CEKI : Jurnal Cendekia Ilmiah, 2024)
This study aims to explore the use of mobile applications in zakat management, identify its benefits, and assess the challenges faced in its implementation. This study uses a qualitative method with a literature review approach. Data were collected through an analysis of relevant literature on zakat management and mobile technology. Data analysis was conducted inductively to identify emerging themes and patterns from the literature. The results of the study indicate that the use of mobile applications in zakat management offers significant advantages, including increased efficiency, transparency, and accuracy in the payment and distribution processes. Mobile applications allow muzakki to pay zakat anytime and anywhere, reducing time and location constraints.